An Analysis of Electronic Commerce (International Journal of Innovative Research in Computer Science & Technology, 2021)
Globalization and information  technology (IT) have altered how businesses conduct  their operations. The IT system is deployed and integrated  in virtually all businesses who have made significant  investments in IT infrastructure for the long-term  development of their business. The use of e-commerce  (EC) as a means of conducting commercial transactions is  causing growing concern. The global economy is  undergoing a transformation. Through the use of internet  technology, all businesses are converted into information based operations. The rate of technological change is now  so rapid that contemporary internet commerce is causing  major economic changes that are affecting every sector.  The Internet has broadened the scope of businesses. The  enormous amount of business information made available  by the worldwide network that enables the collection of  information between companies, corporations, their  customers, and different business divisions is growing at  an exponential rate. Virtual value chains built on  information are critical to every company's operational  and strategic success. The significance, facilitators,  advantages, difficulties, and extent of electronic  commerce in the Indian market were addressed in this  review study.
Keywords: Business; Consumer; Electronic Commerce; Internet; Market Strategy; Profit